Multi-objective Optimization Design of Sleeve Roller Chain Transmission based on Differential Evolution Algorithm - Liu Wei; Lu Qingbo (Jixie chuandong)
The optimum design of sleeve roller chain transmission is most researched by the single objective optimization.A multi-objective optimization model of this problem is established by maximum single row chain transmission efficiency and maximum fatigue life.A modified constrained handling strategy and rounding strategy are incorporated into the multi-objective differential evolution algorithm based on gauss mutation and a multi-objective mixed-discrete variables differential evolution algorithm is proposed.The engineering example shows that the optimum results meet the design requirements and the new algorithm is effective and has certain value for other engineering problem.